2019
DOI: 10.1371/journal.pone.0211143
|View full text |Cite
|
Sign up to set email alerts
|

Examining individual and geographic factors associated with social isolation and loneliness using Canadian Longitudinal Study on Aging (CLSA) data

Abstract: BackgroundA large body of research shows that social isolation and loneliness have detrimental health consequences. Identifying individuals at risk of social isolation or loneliness is, therefore, important. The objective of this study was to examine personal (e.g., sex, income) and geographic (rural/urban and sociodemographic) factors and their association with social isolation and loneliness in a national sample of Canadians aged 45 to 85 years.MethodsThe study involved cross-sectional analyses of baseline d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
112
6
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 134 publications
(141 citation statements)
references
References 66 publications
6
112
6
2
Order By: Relevance
“…Beer et al (2016) studied the geographical distribution of social isolation in Australia's older adults and found that social isolation was most acute in both the largest urban centers (i.e., Sydney and Melbourne) and the most sparsely settled regions of South and West Australia. Menec et al (2019) studied individual-level (i.e., sex, income, relationship status) and regional-level (i.e., rural/urban, sociodemographic factors) predictors of social isolation and loneliness in Canada. They showed that socially isolated individuals were clustered into areas with lower-income older adults, but no relations for regional-level predictors and loneliness were found.…”
Section: A Socioecological Perspective On Lonelinessmentioning
confidence: 99%
“…Beer et al (2016) studied the geographical distribution of social isolation in Australia's older adults and found that social isolation was most acute in both the largest urban centers (i.e., Sydney and Melbourne) and the most sparsely settled regions of South and West Australia. Menec et al (2019) studied individual-level (i.e., sex, income, relationship status) and regional-level (i.e., rural/urban, sociodemographic factors) predictors of social isolation and loneliness in Canada. They showed that socially isolated individuals were clustered into areas with lower-income older adults, but no relations for regional-level predictors and loneliness were found.…”
Section: A Socioecological Perspective On Lonelinessmentioning
confidence: 99%
“…Sullivan and Victor [25] At the macro-level, there is comparatively little research examining the distribution of loneliness geographically and considering how area based factors, such as deprivation or rural/urban typology are associated with loneliness in later life [19,26]. Age UK produced loneliness 'heat maps' for 32,844 neighbourhoods in England [27] focused upon helping target resources at areas most 'in need' but did not investigate how and why loneliness may vary between different types of geographical areas. This work replicates the 'loneliness maps' generated by Dorling [28].…”
Section: Factors Related To Loneliness In Later Lifementioning
confidence: 99%
“…Studies drawing comparisons of individual-based loneliness between deprived and non-deprived areas or rural and urban areas for older adults are less numerous. At a national level, Menec and colleagues looked at the distribution of loneliness across Canada [32]. They used a single item from the CES-D which asks about loneliness in the last week and concluded that there was no difference in loneliness prevalence between rural (9%) and urban (10%) areas.…”
Section: Factors Related To Loneliness In Later Lifementioning
confidence: 99%
“…Furthermore, depression can lead to low physical activity, while loneliness is known to be highly prevalent among older people with depression . We also adjusted for setting (ie, rural or urban) as it is known that older people living in cities are often less physical active, while urban living may influence loneliness . Finally, we adjusted for household size (1, 2, and 3 or more) and social cohesion in the community to assess the independent effect of loneliness regardless of social ties.…”
Section: Introductionmentioning
confidence: 99%